A circular shape arc slot ultra-wideband antenna for biomedical applications - Mohd Ibrahim, Imran; Kiani, Saad Hassan; Awan, Dawar; Bashir, Shahid; Bari, Inam; Bashir, Muhammad Adil; Ali, Haider; Savci, Huseyin Serif; Zakaria, Zahriladha (Korean Institute of Electromagnetic Engineering and Science, 2024)
In modern communication systems, ultra-wideband (UWB) technology has garnered substantial attention due to its superior attributes compared to traditional narrowband communication systems. Over the past decade, UWB technology has also found applications in microwave-based imaging systems. This study introduces a simple planar coplanar waveguide-fed circular shape arc slot antenna designed specifically for biomedicine and microwave medical imaging applications. The proposed design is implemented on a 1.6-mm-thick FR4 substrate with a relative permittivity of 4.4 and a loss tangent of 0.0009. The antenna has physical dimensions of 26 mm × 29 mm and achieves an impressive bandwidth of 16.6 GHz, spanning 2.4 to 19 GHz. It exhibits a peak gain of 2.5 dBi and consistent omnidirectional radiation characteristics. Thorough temporal analysis validates the antenna's performance within acceptable limits, which is further affirmed through practical fabrication and testing, demonstrating strong agreement with simulation results.